6x+9+7y-2x+3=

Simple and best practice solution for 6x+9+7y-2x+3= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+9+7y-2x+3= equation:


Simplifying
6x + 9 + 7y + -2x + 3 = 0

Reorder the terms:
9 + 3 + 6x + -2x + 7y = 0

Combine like terms: 9 + 3 = 12
12 + 6x + -2x + 7y = 0

Combine like terms: 6x + -2x = 4x
12 + 4x + 7y = 0

Solving
12 + 4x + 7y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + 4x + -12 + 7y = 0 + -12

Reorder the terms:
12 + -12 + 4x + 7y = 0 + -12

Combine like terms: 12 + -12 = 0
0 + 4x + 7y = 0 + -12
4x + 7y = 0 + -12

Combine like terms: 0 + -12 = -12
4x + 7y = -12

Add '-7y' to each side of the equation.
4x + 7y + -7y = -12 + -7y

Combine like terms: 7y + -7y = 0
4x + 0 = -12 + -7y
4x = -12 + -7y

Divide each side by '4'.
x = -3 + -1.75y

Simplifying
x = -3 + -1.75y

See similar equations:

| 8+6x=-22+x | | 4x-8+3x=60-2x+3x | | t*4-4=11 | | P^2=5p+84 | | 10y-3=8y+7 | | x+88+127=180 | | 3-2(2-x)=8 | | x+88=127 | | 88+127=x | | 2x+3(x+3)=x+3 | | 3.02+d=2.91 | | 4n+8n= | | 13000.00+25000x=27500x | | x+66=117 | | 3x^2+48x-300=0 | | .12x+x=273.16 | | 4(x-3)+4=21 | | 12212n=-48 | | 6x+17=24-3x | | a^5+5=15 | | 2x+y=270 | | 0=-4sin(2x) | | 4n+6=27-3n | | lx-9l=18 | | 8x^2-2x=-1 | | 2x+9x-8x=13+2 | | (5h-6)=x^2-5x-3 | | (4x-6)(8-x)=0 | | 4(5x-1)-2(2x-11)=15x+15 | | 11x-(2-x)=52 | | f(5h-6)=x^2-5x-3 | | 3-(-12)=4a-a |

Equations solver categories